SOX17 Regulates Conversion of Human Fibroblasts Into Endothelial Cells and Erythroblasts by Dedifferentiation Into CD34(+) Progenitor Cells - Zhang, Lianghui (Circulation, 2017)
BACKGROUND: The mechanisms underlying the dedifferentiation and lineage conversion of adult human fibroblasts into functional endothelial cells have not yet been fully defined. Furthermore, it is not known whether fibroblast dedifferentiation recapitulates the generation of multipotent progenitors during embryonic development, which give rise to endothelial and hematopoietic cell lineages. Here we established the role of the developmental transcription factor SOX17 in regulating the bilineage conversion of fibroblasts by the generation of intermediate progenitors. METHODS: CD34(+) progenitors were generated after the dedifferentiation of human adult dermal fibroblasts by overexpression of pluripotency transcription factors. Sorted CD34(+) cells were transdifferentiated into induced endothelial cells and induced erythroblasts using lineage-specific growth factors. The therapeutic potential of the generated cells was assessed in an experimental model of myocardial infarction. RESULTS: Induced endothelial cells expressed specific endothelial cell surface markers and also exhibited the capacity for cell proliferation and neovascularization. Induced erythroblasts expressed erythroid surface markers and formed erythroid colonies. Endothelial lineage conversion was dependent on the upregulation of the developmental transcription factor SOX17, whereas suppression of SOX17 instead directed the cells toward an erythroid fate. Implantation of these human bipotential CD34(+) progenitors into nonobese diabetic/severe combined immunodeficiency (NOD-SCID) mice resulted in the formation of microvessels derived from human fibroblasts perfused with mouse and human erythrocytes. Endothelial cells generated from human fibroblasts also showed upregulation of telomerase. Cell implantation markedly improved vascularity and cardiac function after myocardial infarction without any evidence of teratoma formation. CONCLUSIONS: Dedifferentiation of fibroblasts to intermediate CD34(+) progenitors gives rise to endothelial cells and erythroblasts in a SOX17-dependent manner. These findings identify the intermediate CD34(+) progenitor state as a critical bifurcation point, which can be tuned to generate functional blood vessels or erythrocytes and salvage ischemic tissue.